The Intersection of Leaving Care and Homelessness: A Literature Overview in a Nordic Welfare State Context - Dokkedal, Alberte Alsø; Niemi, Veera; Freysteinsdóttir, Freydís; Mølholt, Anne-Kirstine; Bengtsson, Mattias; Paulsen, Veronika; Sigurðardóttir, Eva Dögg (Scandinavian University Press, 2026)
Care leavers are significantly overrepresented among young homeless people, a phenomenon that can be found internationally as well as within the Nordic countries. However, we argue that leaving care and homelessness are two distinct research fields, despite overlapping target groups and challenges. While both fields are aware of the intersection of leaving care and homelessness, the issue is perceived from different perspectives. In this article, we provide an overview of the literature on homelessness and the risk of homelessness among care leavers in the Nordic countries (Denmark, Finland, Iceland, Norway and Sweden) to highlight the literature gap at the intersection of leaving care and homelessness research. We particularly emphasise the transition from leaving care to an independent adult life. We reviewed the literature comprising extant research studies and grey literature in the native languages of all five aforementioned Nordic countries, as well as the literature in English, with an emphasis on the Nordic context. The objective is to present a synthesis of the Nordic literature from these perspectives while also acknowledging some differences between the countries. Our analysis indicates that homelessness is addressed in the leaving-care literature, and vice versa, from the perspectives of quantification, understanding the risk for homelessness among care leavers, and challenges in transitions between child and adult welfare services. However, the literature at the intersection is overall very scattered, and more comprehensive and nuanced analysis is needed.